Kajian Arkeologi Mengenai Keraton Surosowan Banten Lama, Banten - Permana, R. Cecep Eka (Makara Human Behavior Studies in Asia, 2004)
This research intrinsically is about activity of field and non-field archaeology. Focus of this research is to know form, settlement, and room function and/or building specially undercarriage building structure which still can be seen in Surosowan keraton. Methods used for the research are excavation, bibliography study, artifact and feature analysis, special analysis, and reconstruction. The result may indicate that, according to ancient map analysis, Surosowan keraton at least have experienced of five development phase. Excavation can only show the existence of is biphase of development pursuant to building structure indication which is overlap. According to tiling remains in every room, this research can reconstruct measure and pattern of tiling installation at every room in complex of keraton. The Research also obtain data to reconstruct building wall brick couple pattern and foundation at building in complex of keraton. Meanwhile, according to field observation is also obtained an assumption for some building function which have been shown, like sultan’s residence, audience hall, garden pool of Roro Denok, and bath of Pancuran Mas.